A Comparison of Different Thyroid Imaging Reporting and Data Systems to Reduce Unnecessary FNAs and Missed Malignancies. (March 2022) - Seif, Ehsan; Qorbani, Mostafa; Mousavi, Shaghayegh; Salahshoor, Ali
Objective: The Thyroid Imaging Reporting and Data System (TIRADS) has been proposed to reduce the number of unnecessary fine needle aspirations (FNA) from thyroid nodules. Materials and Methods: An individual radiologist provided sonographic examinations and FNA on a collection of 188 thyroid nodules. The recommendations based on the TIRADS system, for each nodule, was determined and evaluated against the cytology results. Results: The American College of Radiology (ACR), artificial intelligence (AI), European (EU), and Korean (K) scoring systems reduced FNAs by 53%, 56%, 48%, and 28%, respectively. Among those lesions without a recommendation for immediate FNA, The ACR would have missed four malignant nodules, the AI would have missed four malignant nodules, and K TIRADS would have missed three malignant nodules but with a recommended follow-up imaging. The ACR would have missed three malignant nodules, the AI would have missed four malignant nodules, and EU TIRADS would have missed four malignant nodules, without a recommended follow-up examination. The highest and lowest kappa interrelated agreements were between ACR and AI (0.902) and AI and K (0.448). Conclusion: The ACR and AI TIRADS could substantially decrease the number of FNAs but rely on follow-up imaging. The EU TIRADS reduced the number of FNAs, the least however this system had less dependence on follow-up imaging. The K TIRADS was the most conservative method and the least dependent on follow-up diagnostics.